Effects of cachaça, a typical Brazilian alcoholic beverage, on submandibular glands of rats: a histomorphometric and biochemical study - Dal Prá, Ketelin Juliane [UNESP]; de Fatima Moraes da Silva, Aneliza [UNESP]; Chaves-Neto, Antonio Hernandes [UNESP]; Soubhia, Ana Maria Pires [UNESP] (Springer Nature, 2020)
Objective: This study aimed to evaluate the effects of chronic consumption of cachaça, a Brazilian beverage containing alcohol, on submandibular glands (SM) of rats by using histomorphometric and biochemical parameters. Materials and methods: Twenty-four male rats (40 days of age) were assigned into the following four groups (n = 6): two control groups for 75 days (C75) and 105 days (C105), and two experimental groups of cachaça ingestion with ascending concentrations for consecutive 75 days (CA75) and 105 days (CA105). On the right SM glands, the striated, granular and acini ducts were processed for histomorphometric analysis. The left SM glands were weighed and stored at − 80 °C, to evaluate through biochemical tests carried out by spectrophotometric methods, the functional activity of total acid phosphatase (TAP), tartrate-resistant acid phosphatase (TRAP), and alkaline phosphatase (ALP) and to determine the mucin levels. Results: The absolute and relative weights of the SM glands in both experimental groups were reduced in relation to the controls (p < 0.05). The histomorphometric analysis showed a significant reduction of the acini area (p < 0.05) and non-relevant reduction of striated ducts (p > 0.05). The granular ducts did not show a significant increase of the area (p > 0.05). The TAP and TRAP activities were significantly decreased in the experimental groups (p < 0.05), while the ALP functional activity decreased moderately (p > 0.05). Mucin levels also had a significant reduction when compared with the control groups (p < 0.05). Conclusions: Chronic consumption of cachaça can cause morphological changes associated with glandular atrophy, loss of biochemical functionality of phosphatases, and the reduction of mucin synthesis. Clinical relevance: The consumption of cachaça can compromise the functions of the submandibular glands by altering their morphology and enzymatic activity.
Keywords: Acid phosphatase; Alcoholism; Alkaline phosphatase; Cachaça; Mucin; Submandibular gland